Fenomena Komplain Nasabah PAYDI PT Axa Mandiri Financial Services terhadap Kinerja Perusahaan (Studi Kasus pada PT AMFS Jember Area) - Fitria Tidarina; Siti Maria Wardayati; Alwan Sri Kustono (ITB AAS INDONESIA, 2022)
This study aims to explore the complaint phenomenon from Axa Mandiri Finansial Services customer in the Jember area. This is a qualitative research with a case study approach. The research took place at the Mandiri Jember area form 2020 to 2021. Choosing field research to understand study in-depth situations . The researcher observes, records, interview, explores sources that are closely related to the events that occurred at that time. The result of this study that complaints have an impact on customer’s buying interest ad FA’s convidence to sell insurance products. RBC helps FA to assure customer that the company in the good condition. The Resechers found indication of fraud in several customer complaints cases. Finally, the implementation of EDS has proven to be affective in reducing the number of fraud and avoiding complaints in the future. FA need a condusive environment to get positive vibes to improve theirs performance. Their good performance help company to increase its solvency.